Ocean Global Warming Impacts on the South America Climate - Ramos da Silva, Renato; Haas, Reinaldo (Frontiers in Earth Science, 2016)
The global Ocean-Land-Atmosphere Model (OLAM) model was used to estimate the impacts of the global oceanic warming on the climate projections for the 21st Century focusing on the South America region. This new model is able to represent simultaneously the global and regional scales using a refining grid approach for the region of interest. First, the model was run for a 31-year control period consisting on the years 1960-1990 using the monthly Sea Surface Temperature (SST) from the Atmospheric Model Intercomparison Project (AMIP) data as a driver for the ocean fluxes. Then, the model was run for the period 2010-2100 using the monthly projected SST from the Hadley Center model (HadCM3) as a driver for the oceanic changes. The model was set up with an icosahedral triangular global grid having about 250 km of grid spacing and with a refining grid resolution with the cells reaching about 32 km over the South America region. The results show an overall temperature increase mainly over the center of the Amazon basin caused by the increase of the greenhouse effect of the water vapor; a decrease on precipitation mainly over the northeast Brazil and an increase in the south and over the western Amazon region; and a major increase on the near surface wind speed. These results are similar to the global coupled models; however, OLAM has a novel type of grid that can provide the interaction between the global and regional scales simultaneously.